Estimates of the abundance of minke whales (Balaenoptera acutorostrata) from Faroese and Icelandic NASS shipboard surveys - Pike, Daniel G; Gunnlaugsson, Thorvaldur; Víkingsson, Gísli A; Desportes, Geneviève; Bloch, Dorete (NAMMCO Scientific Publications, 2009)
North Atlantic Sightings Surveys for cetaceans were carried out Northeast and Central Atlantic in 1987, 1989, 1995 and 2001. Here we provide estimates of density and abundance for minke whales from the Faroese and Icelandic ship surveys. The estimates are not corrected for availability or perception biases. Double platform data collected in 2001 indicates that perception bias is likely considerable for this species. However comparison of corrected estimates of densityfrom aerial surveys with a ship survey estimate from the same area suggests that ship surveys can be nearly unbiased under optimal survey conditions with high searching effort. There were some regional changes in density over the period but no overall changes in density and abundance. Given the recent catch history for minke whales in this area, we would not expect to see changes in abundance due to exploitation that would be detectable with these surveys.